The Influence Of Brand Ambassadors on Purchasing Decisions in E-Commerce in Students Majoring in Administrative Science, Makassar State University - Insani, Aisyah Aulia; Jamaluddin; Muh. Rizal S (Business Research and Administration Innovation, 2025)
This research examines the influence of brand ambassadors on purchasing decisions in e-commerce for students of the Department of Administrative Sciences, Makassar State University. The purpose of this study was to determine the level of brand ambassadoronto students of the Department of Administrative Sciences, Makassar State University, to determine the level of purchasing decisionsonto students of the Department of Administrative Sciences, Makassar State University, and to find out the influence of brand ambassadors on purchasing decisions in e-commerce for students of the Department of Administrative Sciences, Makassar State University. This research approach is quantitative. This research was carried outinDepartment of Administrative Sciences, Makassar State University. Sources of data in the study arestudent atDepartment of Administrative Sciences, Makassar State Universityin June to July 2022. Data collection techniques in the form of observation, questionnaires (questionnaires), interviews, and documentation. Data analysis techniques in the form of validity test, reliability test, normality test, descriptive analysis, simple linear regression analysis, correlation coefficient analysis, and analysis of the coefficient of determination. The results of the study indicate that the indicators used in each of these variables indicate where the brand ambassador is in the very good category. The indicators on the purchasing decision variables are in the good category. Based on the correlation test, there is a very strong relationship between the two variables. It can be concluded that there are The Influence of Brand Ambassadors on Purchase Decisions in E-Commerce for Students in the Department of Administrative Sciences.